FRI0039 An acetyl-histone mimetic blocks inflammatory activation of rheumatoid arthritis fibroblast-like synoviocytes. (23rd January 2014) - Kabala, P.; Grabiec, A. M.; Smithers, N.; Witherington, J.; Tak, P. P.; Prinjha, R. K.; Reedquist, K. A.
Abstract : Background: Genetic backgrounds and environmental factors do not completely explain the etiology of disease and predisposition to rheumatoid arthritis (RA), and increasing attention has turned to the potential contributions of heritable epigenetic mechanisms such as DNA methylation, post-translational modifications of histones, and expression of non-coding microRNAs. Fibroblast-like synoviocytes (FLS) isolated from affected joints of RA patients maintain an aggressive phenotype in vitro, indicating potential alteration of epigenetic regulatory processes, and changes in global and gene-specific promoter DNA methylation and histone modification are observed in RA FLS. I-BET compounds, acetyl histone mimetics which interfere with reading of acetylated histones by BET family bromodomain proteins BRD2-4, prevent LPS-induced inflammatory gene expression in murine bone marrow-derived macrophages in vitro, as well as in vivo models of endotoxic shock and bacterial sepsis. Objectives: This study was undertaken to assess the potential of I-BET to influence the inflammatory activation of RA FLS. Methods: RA fibroblast-like synoviocytes (FLS) were treated with IL-1β or TNF in the presence or absence of increasing concentrations of I-BET, and IL-6 and IL-8 production measured by ELISA. Cellular viability was assessed using MTT assay and cell death ELISA kits. Activation of intracellular signaling pathways was examined by immunoblotting. Total RNA was extracted and mRNA expression of genes regulated by IL-1β or TNF in RA FLS was analyzed using a low density quantitative PCR custom array. Results: BRD2-4 mRNA expression was readily detected in RA FLS. I-BET reduced RA FLS (n=6) production of IL-6 protein in response to IL-1β (1 μM, 70% reduction, P < 0.001) and TNF (50%, P < 0.001). IL-8 production in response to IL-1β (>75% reduction, P <. 0.001) and TNF (>70%, P < 0.001) was also inhibited. Similar effects were observed on IL-6 and IL-8 mRNA expression. Inhibition of IL-6 and IL-8 production was maintained when I-BET treatment was delayed 1-4 hours post-stimulation. I-BET had no effect on cell viability or survival, and failed to modulate IL-1β or TNF–induced activation of MAPK or NF-κB signaling pathways. Low density qPCR array analysis of 26 genes induced by IL-1β in RA FLS (n=3) demonstrated that I-BET reduced induction of 17 genes by >50%, including TNF (>80% suppression), MMP-1 (>90%), MMP-3 (90%), SELE (>80%), VCAM-1 (>60%), CXCL-6 (>75%), CXCL-9 (>95%) and CXCL-11 (>90%). Conclusions: Our results demonstrate that disrupting the recruitment of BET family proteins to acetylated histones efficiently blocks RA FLS production of inflammatory mediators, including cytokines, chemokines and MMPs, in response to IL-1β and TNF. This study provides initial evidence that the development of synthethic compounds targeting interactions between epigenetic modifications, such as histone acetylation, and the proteins which interpret these modifications may have therapeutic potential in the treatment of RA. Disclosure of Interest: P. Kabala: None Declared, A. Grabiec: None Declared, N. Smithers Shareholder of: GlaxoSmithKline, Employee of: GlaxoSmithKline, J. Witherington Shareholder of: GlaxoSmithKline, Employee of: GlaxoSmithKline, P. Tak Shareholder of: GlaxoSmithKline, Employee of: GlaxoSmithKline, R. Prinjha Shareholder of: GlaxoSmithKline, Employee of: GlaxoSmithKline, K. Reedquist Grant/research support from: GlaxoSmithKline